Engineering 2D Architectures toward High‐Performance Micro‐Supercapacitors. Issue 1 (22nd August 2018) - Da, Yumin; Liu, Jinxin; Zhou, Lu; Zhu, Xiaohui; Chen, Xiaodong; Fu, Lei
Abstract: The rise of micro‐supercapacitors is satisfying the demand for power storage in portable devices and wireless gadgets. But the miniaturization of the energy‐storage components is significantly limited by their energy density. Electrode materials with adequate electrochemical active surfaces are therefore required for improving performance. 2D materials with ultralarge specific surface areas offer a broad portfolio of the development of high‐performance micro‐supercapacitors in spite of their several critical drawbacks. An architecture engineering strategy is therefore developed to break these natural limits and maximize the significant advantages of these materials. Based on the approaches of phase transformation, intercalation, surface modification, material hybridization, and hierarchical structuration, 2D architectures with improved conductivity, enlarged specific surface, enhanced redox activity, as well as the unique synergetic effect exhibit great promise in the application of miniaturized supercapacitors with highly enhanced performance. Herein, the architecture engineering of emerging 2D materials beyond graphene toward optimizing the performance of micro‐supercapacitors is discussed, in order to promote the application of 2D architectures in miniaturized energy‐storage devices. Abstract : Recent advancement in 2D architecture engineering toward high‐performance micro‐supercapacitors is comprehensively reviewed. 2D materials with reduced size meet the demands of micro‐supercapacitors. Architecture engineering strategies based on phase transformation, intercalation, surface modification, material hybridization, and hierarchical structure are therefore developed to break their natural limits and maximize the significant advantages of these materials, thus opening up new opportunities to develop high‐performance miniaturized devices.